Can non-fortified marine salt cover human needs for iodine?. (3rd April 2019) - Lobato, Carolina B.; Machado, Ana; Mesquita, Raquel B. R.; Lima, Lurdes; Bordalo, Adriano A.
Abstract: Iodine deficiency remains a worldwide problem with two billion individuals having insufficient iodine intake. Universal salt iodisation was declared by UNICEF and WHO as a safe, cost-effective, and sustainable way to tackle iodine deficiency. In Portugal, the few studies available unravel an iodine status below the WHO guidelines for pregnant women and school-aged children. In the present study, the iodine levels of household salt consumed in Portugal was assessed, for the first time. Non-iodised (median 14 ppm) and fortified (median 48 ppm) marine salt samples showed iodine levels lower than the minimum and above the maximum threshold recommended by non-mandatory Portuguese law and WHO recommendations, respectively. This study calls attention to the fact that marine salt per se, in spite of containing a natural high amount of iodine, requires further fortification in order to be used as an effective tool to deal with iodine insufficiency.